Pengaruh Lingkungan Kerja dan Kompetensi Terhadap Kinerja Pegawai ASN dengan Motivasi sebagai Variabel Intervening pada Sekretariat Daerah Kota Padang - Muhammad Irvandhel; Yulasmi Yulasmi; Zefriyenni Zefriyenni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of the work environment and competence on the performance of ASN employees with motivation as an intervening variable in the Padang City Regional Secretariat. The type of research used is quantitative. Data collection was carried out through distributing a questionnaire of 120 respondents to employees of the Padang City Regional Secretariat, the questionnaire returned 99 respondents. Data analysis techniques are multiple linear regression analysis and path analysis. The results of the study were obtained that the work environment has a positive and significant effect on the performance of employees at the Padang City Regional Secretariat. Competence has a positive and significant effect on employee performance at the Padang City Regional Secretariat. The work environment has a positive and significant effect on motivation at the Padang City Regional Secretariat. Competence has a positive and significant effect on motivation at the Padang City Regional Secretariat. Motivation has a positive and significant effect on employee performance at the Padang City Regional Secretariat. The work environment has a positive and significant effect on employee performance through motivation at the Padang City Regional Secretariat. Competence has a positive and significant effect on employee performance through motivation at the Padang City Regional Secretariat. The contribution of work environment, competence, and motivation to employee performance was 0.609 or 60.9%.